Um mapeamento sistemático sobre ferramentas de desenvolvimento em realidade aumentada para o reconhecimento de plantas medicinais - Sá, Raison Robert Monteiro de (Brasil, 2021)
The usage of medicinal herbs to treat illnesses is as old as humanity history, but knowing how to recognize, conserve and use each type of herb is fundamental for effectiveness of natural treatments. In this sense, this work aims to carry out a survey and analysis of the main application tools found on the subject through systematic mapping, and also present the interaction assessment of an app that identifies medicinal herbs, in addition, reports the forms of use and preparation of medicinal herbs. These applications handle specifically on the recognition of medicinal plants for natural treatment of diseases. The results of this work may contribute to the development of future research and tools related about this research.